DEVELOPMENT OF SLINGSHOT BALL LEARNING MEDIA FOR EMOTIONAL DEVELOPMENT IN EARLY CHILDHOOD IN CEMPAKA KINDERGARTEN - Sulastya Ningsih; Elva M Sumirat; Nurul Aini MM Sodik; Sri Rawanti (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2025)
Emotional development in children is a major factor that influences their attitudes, values, and behavior in the future. This development aspect requires special attention because it must be fostered from the beginning. This study aims to create a product that can be used as a means in the learning process, namely "Slingshot Ball," which is designed to support the emotional development of early childhood and act as an educational game media; this study was conducted on early childhood group A at Cempaka Kindergarten, with a total of 25 participants aged 4-5 years. The research method used is Research and Development (R&D), following the steps Borg and Gall developed through structured stages. Based on the evaluation of media experts, Slingshot Ball scored 35 with an average of 4, which is included in the "very good" category. (26.17 <X ≤ 32.63). Meanwhile, the assessment of material experts showed that the Slingshot Ball media scored 28 with an average of 4.3, which is included in the "good" category (23.76 <X ≤ 29.28). Group trials show that this media is efficient and falls into the "very developed" category in encouraging the emotional progress of early childhood, with a score of 90%. Therefore, the Slingshot Ball media is worthy of being used by educators as an interactive learning tool to support the emotional development of early childhood.